Summary and derived Risk Assessment of 3D printing emission studies. (1st February 2023) - Romanowski, Heike; Bierkandt, Frank S.; Luch, Andreas; Laux, Peter
Abstract: Three-dimensional (3D) printing is an additive manufacturing process that increases in application and consumer popularity. Studies with 3D printers have shown that the printing process releases particles and volatile organic compounds (VOCs). This review looked at 50 studies that analyzed the most commonly used printing process in consumer 3D printers, the material extrusion or so-called fused filament fabrication (FFF) method and summarizes the most important results. Although the reviewed studies often used different methods, general assumptions can be drawn: Higher printing temperature resulted in higher emissions, styrene was the main VOC emitted during printing with ABS, the size of released particles was in the nano range and filaments with additives could pose a higher risk due to the possible release of e.g., carbon nanotubes (CNTs). In vivo and in vitro studies showed toxic effects. Thus, we recommend: printing in a separated and ventilated room, using the lowest possible print temperature and be cautious with filaments containing particulate additives. Highlights: Review of 50 published studies covering the emissions of 3D printing. Summary of methods, results, toxicological studies and methods to reduce emissions. 3D printing releases harmful nanoparticles and VOCs. Filaments with additives pose a higher risk due to the possible release of e.g., CNTs. Styrene is the most reported VOC for ABS 3D printing.